A SCANO Nomogram for Individualized Prediction of the Probability of 1-Year Unfavorable Outcomes in Chinese Acute Ischemic Stroke Patients - Li, Xiang; Wang, Fusang; Zhao, Zhihong; Sun, Chao; Liao, Jun; Li, Xuemei; Huang, Chaoping; Nyame, Linda; Zhao, Zheng; Zheng, Xiaohan; Zhou, Junshan; Li, Ming; et al. (Frontiers in Neurology, 2020)
Background and purpose: Accurate prediction of functional outcome after stroke would provide evidence for reasonable post-stroke management. This study aimed to develop and validate a nomogram for individualized prediction of 1-year unfavorable outcome in Chinese acute ischemic stroke (AIS) patients. Methods: We retrospectively gathered AIS patients at the National Advanced Stroke Center of Nanjing First Hospital (China) between August 2014 and May 2017 within 12h of symptoms onset. The outcome measure was 1-year unfavorable outcome (modified Rankin Scale 3 - 6). To generate the nomogram, pre-established predictors were entered into a logistic regression model. The discriminative performance of the SCANO nomogram was assessed by the area under the receiver-operating characteristic curve (AUC-ROC) and calibration by the Hosmer-Lemeshow test. Results: A total of 807 patients were included into this study, and 262 (32.5%) of them had unfavorable outcomes. Systolic blood pressure, Creatinine, Age, National Institutes of Health Stroke Scale (NIHSS) score on admission, and fasting blOod glucose were significantly associated with unfavorable outcome and entered into the SCANO nomogram. AUC-ROC of SCANO was 0.795 and calibration was good (p = 0.360 for the Hosmer-Lemeshow test). Conclusions: The SCANO nomogram is developed and validated in Chinese AIS patients to firstly predict 1-year unfavorable outcome, which is simple and convenient for stroke patient management.